Estrategia íconos verbales y comprensión de textos en enseñanza remota en niños de cinco años de la Institución Educativa Inicial Victoria Barcia Boniffatti, Iquitos 2021 - Saenz Fasabi, Jhoari Chris (2023)
The relevant aspects carried out in the present investigation are concisely shown, raising the following question: What is the relationship between the verbal icon’s strategy and text comprehension in remote teaching in five-year-old children of the Victoria Barcia Boniffatti Initial Educational Institution? Iquitos 2021? and with the purpose of: Relating the methodology of verbal icons and text comprehension in remote teaching in five-year-old children from the Victoria Barcia Boniffatti Initial Educational Institution. The relational type of research is used, with a non-experimental, cross-sectional, field, and bivariate design. The population and sample were 162 children of initial education. The survey technique and two questionnaires were used as instruments, which were validated by specialists in the field. It is conclusive that there is a preponderant relationship between the verbal icon’s strategy and text comprehension in remote teaching, this is because the majority of children who reached a high level when using the verbal icons strategy also reached a high level in the comprehension of texts in the Educational Institution object of the present investigation.